The Effect of Promotion, Word of Mouth and Digital Marketing on Consumer Satisfaction through the Insurance Policy Purchase Decision Using Fuse Pro Application - Hasanudin Hasanudin; Andini Nurwulandari; Sari Indah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine and analyze the effect of promotion, word of mouth and digital marketing on consumer satisfaction with policy purchase decisions using the FUSE PRO application. In this study, data were collected using a questionnaire with the population taken, namely Consumer Satisfaction with Purchase Decisions at FUSE on all partners or insurance agents who use the FUSE PRO application with a total sample of 215 respondents. The results of this study can be concluded into several parts, namely: 1) The influence of promotion, word of mouth and digital marketing has a positive and significant impact in improving purchasing decisions at the company. 2) Promotion, word of mouth and digital marketing also have a positive and significant impact that will affect satisfaction at FUSE, and 3) Promotion, word of mouth and digital marketing also have a positive and significant impact with increasing purchasing decisions that have an impact on consumer satisfaction.